Application of Accentuated Eccentric Loading to Elicit Acute and Chronic Velocity and Power Improvements: A Narrative Review - Justin Merrigan; Jonathon Borth; Christopher Taber; Timothy Suchomel; Margaret Jones (International Universities Strength and Conditioning Association, 2022)
Accentuated eccentric loading (AEL) employs heavier load magnitudes in eccentric actions than concentric actions of complete stretch-shortening cycles. In doing so, unique neuromuscular and molecular responses are expected to result in acute post-activation performance enhancements, as evidenced by increased movement velocity or power. Improvements are dependent upon load selection, which varies across exercises, such as jumps and bench press throws (eccentric: 20-40 kg or 20-30% of body mass; concentric: body mass only), and squats and bench press (eccentric: 77.3-120% One-Repetition Maximum (1-RM); concentric: 30-90% 1-RM). The efficacy of AEL is dependent upon the concentric load used, which in turn is influenced by the magnitude of the eccentric load. Greater strength relative to body mass may enable the maintenance of technique and pacing during AEL, necessary for resultant performance enhancements, particularly when using eccentric loads exceeding the individual's concentric 1-RM. Before prescribing AEL practitioners should consider: training experience, strength relative to body mass, the particular exercise, AEL application method, and the magnitude of both eccentric and concentric loads. Thus, the aims of this brief review are to describe: 1) neuromuscular and molecular constructs of AEL; 2) acute effects of AEL; 3) chronic effects of AEL; 4) loading considerations; 5) practical applications.